A novel approach for application of smoothed point interpolation methods to axisymmetric problems in poroelasticity. (October 2018) - Tootoonchi, A.; Khoshghalb, A.; Liu, G.R.
Abstract: A smoothed point interpolation method (SPIM) for the numerical modelling of saturated porous media in axisymmetric conditions is proposed, aiming to overcome the singularity problem encountered when using SPIMs in axisymmetric settings. The singularity is circumvented in this study by decomposition of the property matrices of the system to sub-matrices with smoothed terms and non-smoothed terms. The salient feature of the proposed method is that it neither incurs additional computation nor compromises on the accuracy of the method. The proposed method is examined by numerical modelling of several benchmark axisymmetric problems, along with a set of convergence studies.